2010
DOI: 10.1159/000296293
|View full text |Cite
|
Sign up to set email alerts
|

Is a Single Focus of Low-Grade Prostate Cancer Diagnosed on Saturation Biopsy Predictive of Clinically Insignificant Cancer?

Abstract: Objectives: To evaluate the incidence of indolent prostate cancer (PCa; <0.5 ml cancer and Gleason score, GS, ≤6) in men with microfocal PCa diagnosed on saturation biopsy (SPBx) submitted to radical retropubic prostatectomy. Methods: From January 2005 to December 2008, 413 patients (median age 61.5 years) underwent SPBx (median 30 cores). A single neoplastic microfocus (5% or less of cancer in a single core) was found in 55 men and all patients underwent retropubic prostatectomy. Median PSA was equal to 8.2 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Several studies have demonstrated that even extended "saturation" biopsies performed transrectally do not reliably identify aggressive cancers. 12,13 However, as we demonstrated in an earlier report, 14 TTMB seems to outperform saturation biopsies performed transrectally and is particularly effective at identifying cancers in the anterior prostate, the area most frequently missed by the transrectal approach.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies have demonstrated that even extended "saturation" biopsies performed transrectally do not reliably identify aggressive cancers. 12,13 However, as we demonstrated in an earlier report, 14 TTMB seems to outperform saturation biopsies performed transrectally and is particularly effective at identifying cancers in the anterior prostate, the area most frequently missed by the transrectal approach.…”
Section: Discussionmentioning
confidence: 56%
“…PSA screening for prostate cancer has become widespread, and the occurrence of low-risk prostate cancer has been dramatically increasing [5]. Using definite therapy such as RP, clinically localized prostate cancer might be curatively treated, especially in low-risk prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the Epstein criteria [4], the preoperative diagnosis of low-risk prostate cancer is a difficult decision to make since prostate cancer is a multifocal, heterogeneous disease. Some studies have reported that even low-risk patients may demonstrate disease upgrading or upstaging [5].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between biopsy findings and overall tumor burden is rather poor and even a single focus on low-grade PCa in a biopsy specimen does not predict the pathologic stage of the disease. We have previously observed a statistically significant correlation between the definitive pathologic stage and quantitative histology when performing SPBx [6], but the prediction failed in the presence of a microfocus of cancer where the incidence of OC PCa, extraprostatic extent and surgical margin positivity ranged between 50 and 92%, 6 and 27.3% and 7 and 14.5%, respectively [11,14,22]. SPBx has been proposed as a staging tool for revaluating patients with microfocal PCa [13].…”
Section: Discussionmentioning
confidence: 99%
“…Boccon-Gibod et al [23] reported that in 34 patients submitted to repeat SPBx the presence of multifocal PCa and un-upgrading of GS was true in 70 and 20% of the cases, respectively. Moreover, in 55 patients with microfocal disease who underwent RRP after SPBx we detected a significant cancer in 85% of the cases, with presence of non-OC PCa in 27.3% of them [22]. Thus, the sensitivity of SPBx (i.e.…”
Section: Discussionmentioning
confidence: 99%